Awareness on The Role of Sanitisers In Controlling the Spread of Covid-19 Among Urban Population - CHOPRA, ADITI; ARIVARASU, LAKSHMINARAYANAN; SOMASUNDARAM, DR. JAYALAKSHMI (The journal of contemporary issues in business and government, 2020)
The pandemic of coronavirus has affected millions. The fast spreading virus has to be controlled and preventive measures should be taken. Since there is no vaccine or cure, sanitisers are 99.9% effective against germs and can kill SARS-COV2 by attacking its envelope. Usage of sanitiser is extremely important for the control of spread of coronavirus, and so, people should accordingly stock up on it. A survey questionnaire of 15 questions was conducted to test the awareness of properties of sanitisers and to encourage people to use them, among 100 random sample size belonging to the urban background. Majority of the people think that sanitisers are a convenient and effective way of fighting germs. Since they know that clean hands are the first line of defence in fighting infections, they use it often and accordingly stock up on PPE. Majority of people know the important facts about sanitisers and have started using them. Most people think that sanitisers are useful in controlling the spread of coronavirus and have accordingly increased their usage of it during the global pandemic.